From History to Mindset: The Psychological Legacy of Taxation in Indonesia - Susilawati, Ika Rahma; Hidayat, Rahmat; Lufityanto, Galang (Buletin Psikologi, 2024)
This paper explores the factors contributing to tax non-compliance in Indonesia by examining its psycho-historical context through a chronological literature review. By analyzing multiple written sources, the researchers outlined the historical progression of taxation in a systematic order. Specific terms associated with different types of taxation, such as tribute, head tax, and land rent tax, are utilized to dissect the essence of taxes within the broader economic and social historical framework. Investigating the evolution of taxation from the era of kingdoms to the present revealed how public perceptions of taxes have changed over time—viewed at various points as coerced tribute, extortion, national contribution, corruption, and a duty-bound obligation. These shifting perceptions reflect the deep-rooted psychological significance of taxation within Indonesian society. The study suggests capitalizing on these historical viewpoints, both positive and negative, to enhance tax compliance strategies. By gaining insights into these foundational attitudes regarding taxation, the paper advocates for further empirical research to refine tax representation and improve governance. This approach seeks to develop a nuanced strategy in tax policy, highlighting the importance of aligning with the historical and psychological context of the Indonesian population.Top of Form Bottom of Form